2018
DOI: 10.1186/s12937-018-0361-y
|View full text |Cite
|
Sign up to set email alerts
|

Propolis ethanolic extracts reduce adenosine diphosphate induced platelet aggregation determined on whole blood

Abstract: BackgroundPropolis is a well-known bee product containing more than 2000 identified compounds. It has many beneficial effects on human health that include antibacterial, antiviral, anticancer and hepatoprotective justifying its use as a dietary supplement. Platelet aggregation plays crucial role in thrombus formation that can cause stroke or heart attacks. As cardiovascular diseases, including those caused by thrombus formation, are related to 50% of deaths of Western population, the objective of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…The inhibition of the COX-1 pathway appears to be the most common. However, with the study by Bojic et al [71], the inhibition of the P2Y 12 pathway of activation may result in a decrease in the expression of the GPIIb/IIIa receptor which is involved in crosslinking activated platelets to form platelet aggregates [72]. Overall, however, the rich source of flavonoid and phenolic acids together in propolis may highlight a synergistic anti-aggregatory effect.…”
Section: Impact Of Polyphenols On Platelet Aggregationmentioning
confidence: 97%
See 2 more Smart Citations
“…The inhibition of the COX-1 pathway appears to be the most common. However, with the study by Bojic et al [71], the inhibition of the P2Y 12 pathway of activation may result in a decrease in the expression of the GPIIb/IIIa receptor which is involved in crosslinking activated platelets to form platelet aggregates [72]. Overall, however, the rich source of flavonoid and phenolic acids together in propolis may highlight a synergistic anti-aggregatory effect.…”
Section: Impact Of Polyphenols On Platelet Aggregationmentioning
confidence: 97%
“…Using whole blood impedance, another study evaluated the antiplatelet benefit of polyphenol-rich product propolis. Bojic et al [71] demonstrated that propolis inhibited ADP-induced platelet aggregation in whole blood. The study measured the anti-aggregatory effect of propolis ethanolic extracts in whole blood.…”
Section: Impact Of Polyphenols On Platelet Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers, [235] more recently, checked different propolis samples from Croatia regarding their anti-aggregatory activity on platelet aggregation, and demonstrated that propolis even in low concentrations presented an important anti-aggregatory potential, suggesting that propolis supplementation may influence platelet aggregation, which can play crucial role in thrombus formation responsible of stroke or heart attacks. Moreover, Barbarić et al [68] studied propolis samples from Bosnia and Hercegovina and Croatia regarding its cytotoxic effects on cervical tumor cell line (HeLa), and they found that it exhibited an antiproliferative and cytotoxic effect.…”
Section: Southern European Coast Application In Medicine Pharmacy Anmentioning
confidence: 99%
“…Research in the past decade has demonstrated several health benefits of flavonoids (Kozłowska & Szostak‐Węgierek, ). The mechanisms underlying these health benefits include, but are not limited to, anti‐inflammation, antioxidation, antimicrobial, and antimutagenic effects (Bojić, Antolić, Tomičić, Debeljak, & Maleš, ). Flavonoids are susceptible to CYP metabolism; however, they can also act as enzyme inhibitors and cause clinically significant interactions (Östlund, ).…”
Section: Introductionmentioning
confidence: 99%